Concurrent vascular flow defects at the deep capillary plexus and choriocapillaris layers in acute macular neuroretinopathy on multimodal imaging: A case series - Hwang, Christopher K. (Am J Ophthalmol Case Rep, 2020)
PURPOSE: To describe multimodal imaging findings with focus on retinal and choroidal vascular features in acute macular neuroretinopathy (AMN). OBSERVATIONS: Three eyes from 3 patients (1 man, 2 women) with average age of 31 were included in this retrospective case series at a single institution. Each case showed petaloid hyporeflective areas on infrared images (IR) with variable levels of outer retinal defects on spectral domain optical coherence tomography (OCT). En face OCT angiography (OCT-A) images showed quantifiable reduction in vessel density at levels of the deep capillary plexus (DCP) and choriocapillaris (CC) layers. In 2 of the cases with near-infrared autofluorescence imaging (NIRAF), there were subtle areas of hypoautofluorescence corresponding in location to the lesions seen on IR. In one case, fluorescein angiography (FA) showed a small area of retinal vascular leakage in the area of the IR lesion, and in other 2 cases, there were paracentral areas of hypofluorescence in the area of the IR lesions. En face structural OCT image at the retinal pigment epithelium (RPE) level in each case showed no evidence of projection artifact from the retina. CONCLUSIONS AND IMPORTANCE: The pathogenesis of AMN is suspected to involve a vasogenic insult. However, the precise localization of the vascular insult has been controversial and unclear. Our findings demonstrate that concurrent vascular flow defects in both DCP and CC could be possible in AMN and suggest that an inflammatory and vascular etiology in concert could underlie the pathogenesis of AMN.